2007
DOI: 10.1155/2007/926421
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Thoracic Society Recommendations for Management of Chronic Obstructive Pulmonary Disease – 2007 Update

Abstract: Chronic obstructive pulmonary disease (COPD) is a major respiratory illness in Canada that is both preventable and treatable. Our understanding of the pathophysiology of this complex condition continues to grow and our ability to offer effective treatment to those who suffer from it has improved considerably. The purpose of the present educational initiative of the Canadian Thoracic Society (CTS) is to provide up to date information on new developments in the field so that patients with this condition will rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
146
1
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(160 citation statements)
references
References 0 publications
1
146
1
12
Order By: Relevance
“…With regard to bronchodilator therapy, although there are no controlled studies, there is great consensus on the choice of shortacting bronchodilators, b2-agonist (SABA) and/or short acting muscarinic antagonists (SAMA). [9][10][11][12][13][14][15][16][17]22,23 The administration of short-acting bronchodilators must be of intensive type, every 5-6 h, because their duration of action, in particular for SABA, is only 4-6 h.…”
Section: Management Of Chronic Obstructive Pulmonary Disease In Emergmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to bronchodilator therapy, although there are no controlled studies, there is great consensus on the choice of shortacting bronchodilators, b2-agonist (SABA) and/or short acting muscarinic antagonists (SAMA). [9][10][11][12][13][14][15][16][17]22,23 The administration of short-acting bronchodilators must be of intensive type, every 5-6 h, because their duration of action, in particular for SABA, is only 4-6 h.…”
Section: Management Of Chronic Obstructive Pulmonary Disease In Emergmentioning
confidence: 99%
“…30,31,34 Recently have been recommended shorter cycles of systemic corticosteroid therapy (5 days) 9 compared to traditional 7-14 days. [11][12][13] The continuation of systemic steroid therapy beyond two weeks has not shown advantages on acute exacerbation.…”
Section: Management Of Chronic Obstructive Pulmonary Disease In Emergmentioning
confidence: 99%
“…1 Our study 2 focused on severe COPD exacerbations leading to hospital admission, and the mean number of admissions for an acute exacerbation of COPD in the previous year was about one per patient.…”
Section: [Reply From Authors:]mentioning
confidence: 99%
“…Few studies have been conducted to provide a fair understanding of ACOS manifested by both asthma and COPD symptoms (9,11,12). Studies from the western population have shown the prevalence of ACOS to be 1.8% when diagnosed using spirometry (13) and 2.7% when diagnosed based on self-reported or physician-diagnosed asthma and COPD (14). Furthermore, the prevalence of ACOS (3.2%) was lower than COPD (6.0%) or asthma alone (5.6%) in the United States (15), whereas the percentage of patients visiting emergency departments was high for ACOS than for COPD alone in Korea (16).…”
Section: Introductionmentioning
confidence: 99%